The Sway of Evil on Culture: on The Prince of This World - Hittinger, John (Philosophy and Canon Law, 2024)
In this essay, the connections between philosophy and culture in John Paul II’s Fides et Ratio and Gaudium et Spes are discussed. The orientation towards transcendence can be inhibited by cultural trends and intellectual attitudes. Faith purifies and elevates culture. The designation of Jacques Maritain as a model for the integration of faith and reason is also discussed here. In the light of this recommendation, we consider the argument of Jacques and Raïssa Maritain that culture is under the sway of evil especially through the ministrations of the prince of this world. The passage from Ephesians 6:10 is interpreted as the scriptural source for this view. The thought of John Henry Newman in The Dream of Gerontius is also brought into consideration in reference to the evil sway of the demons. We conclude with a look at the project of the Maritains as an apostolate to culture.